2018
DOI: 10.1155/2018/9865495
|View full text |Cite
|
Sign up to set email alerts
|

Troxerutin Protects Kidney Tissue against BDE‐47‐Induced Inflammatory Damage through CXCR4‐TXNIP/NLRP3 Signaling

Abstract: 2,2′,4,4′-Tetrabromodiphenyl ether (BDE-47) induces oxidative stress in kidney cells, but the underlying mechanism remains poorly understood. Troxerutin, a natural flavonoid, has potential antioxidant and anti-inflammatory efficacy. In this study, we assessed the effect of troxerutin on kidney damage caused by BDE-47 and investigated the underlying mechanism. The results showed troxerutin reduced reactive oxygen species (ROS) level and urine albumin-to-creatinine ratio (ACR), decreased the activities of inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…The body weight of mice was assessed daily prior to administration of the administered treatment to confirm the experimental model of 5-FU induced intestinal mucositis. The TRX doses considered in the current study are in accordance with those in previous published studies [19][20][21][22]61]. daily prior to administration of the administered treatment to confirm the experimental model of 5-FU induced intestinal mucositis.…”
Section: Experimental Protocol Of 5-fu-induced Intestinal Mucositissupporting
confidence: 69%
See 2 more Smart Citations
“…The body weight of mice was assessed daily prior to administration of the administered treatment to confirm the experimental model of 5-FU induced intestinal mucositis. The TRX doses considered in the current study are in accordance with those in previous published studies [19][20][21][22]61]. daily prior to administration of the administered treatment to confirm the experimental model of 5-FU induced intestinal mucositis.…”
Section: Experimental Protocol Of 5-fu-induced Intestinal Mucositissupporting
confidence: 69%
“…daily prior to administration of the administered treatment to confirm the experimental model of 5-FU induced intestinal mucositis. The TRX doses considered in the current study are in accordance with those in previous published studies [19][20][21][22]61]. To investigate the role of cyclooxygenase 2 (COX-2) enzyme during TRX treatment of 5-FUinduced intestinal mucositis, COX-2 was blocked by an intraperitoneal (i.p) injection of 7.5 mg/kg of CLX.…”
Section: Experimental Protocol Of 5-fu-induced Intestinal Mucositismentioning
confidence: 86%
See 1 more Smart Citation
“…It is widely reported that TXR is a phytochemical with proven health benefits. It also has a very low toxicity (LD 50 of 27160 mg/kg body weight in rat) and safe for human use [38][39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…In response to the increased formation of reactive oxygen species (ROS), thioredoxin interacting protein (TXNIP) detaches from thioredoxin (Trx), binds to the nucleotide-binding domain-like receptor protein 3 (NLRP3), and then activates NLRP3 inflammasome [ 8 ]. The activation of the NLRP3 inflammasome results in the maturation and release of pro-inflammatory cytokines, such as interleukin-1β (IL-1β), which further aggravates the production of inflammatory cytokines (tumor necrosis factor-α (TNF-α), IL-6, inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX2)) and induces oxidative stress [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%